Effects of copper and chromium and high temperature on growth, proline and protein content in wheat seedlings - Muslu, Ahmet; Ergün, Nuray (Bangladesh Journal of Botany, 2013)
Effects of interactions between high temperature and chromium (Cr(VI)) and copper (Cu) on wheat (Triticum aestivum L. cv. Dagdas 94) seedlings were investigated. High concentrations of Cr and Cu at 40°C decreased the root and shoot length and dry weight. The total chlorophyll content was decreased at 30 ?M Cr + 40°C. At the high Cr and Cu concentrations, carotenoid content was increased compared to that of control groups. Heavy metal treatment increased proline content but decreased that of soluble protein. In addition, chromium showed greater toxic effects on growth and biochemical parameters than that of Cu. DOI: http://dx.doi.org/10.3329/bjb.v42i1.15871 Bangladesh J. Bot. 42(1): 105-111, 2013 (June)